A Fatal Central Nervous System Enterovirus 68 Infection - Kreuter, Justin D.; Barnes, Arti; McCarthy, James E.; Schwartzman, Joseph D.; Oberste, M. Steven; Rhodes, C. Harker; Modlin, John F.; Wright, Peter F. (Archives of pathology & laboratory medicine (1976), 2011)
The anticipated eradication of poliovirus emphasizes the need to identify other enteroviral causes of severe central nervous system disease. Enterovirus 68 has been implicated only in cases of respiratory illness. We therefore report a case of fatal meningomyeloencephalitis caused by enterovirus 68 in a 5-year-old boy, which required neuropathology, microbiology, and molecular techniques to diagnose.